1, 2, 3, 4... Anthropology and the Fourth World - Graburn, Nelson H. H. (Culture, 1981)
The term the Fourth World comprizes those native peoples whose lands and cultures have been engulfed by the nations of the First, Second and Third Worlds. Parallelling the usage of the term Third World, this term has come into use in the past ten years by scholars interested in the political status of indigenous people in “internal colonies”, and by the leaders of the minority peoples themselves, such as the Dene and the Lapps. This paper discusses (a) the sources of the term, (b) its range of meaning and relation to the term Third World, (c) the consciousness and political reality of the Fourth World, and (d) the problems and usage of the term in anthropology.